ANALISIS DAN PERANCANGAN SISTEM INFORMASI E-LEARNING PADA SMA NEGERI 2 KOTA JAMBI - Simorangkir, Herli; Mulyono, Herry (Jurnal Manajemen Sistem Informasi, 2019)
The need for e-learning learning materials as a tool for monitoring the teaching and learning process ofstudents so that each subject matter can improve learning outcomes. The consequence of this is that theJambi City Public High School 2 must be able to improve the quality and quality of the education itcarries out. Based on observations and interviews with subject teachers of SMA Negeri 2 Jambi City, thepurpose of this study the writer wants to achieve is to analyze and design an e-learning informationsystem at SMA Negeri 2 Jambi City in which there are several methods used in developing this systemincluding Prototype and using system modeling, namely use case diagrams, activity diagrams, and classdiagrams. The method used in this research is data collection techniques using observation andinterviews. The results obtained were in the form of a web-based E-Learning design at SMA Negeri 2Jambi City. With e-learning can provide convenience for students to do distance learning or online, sothat teachers can conduct monitoring activities even though they are outside of school